Pengaruh Suplementasi L-Threonine dalam Pakan terhadap Kinerja Organ Dalam Ayam Broiler - Serfina Kolo; Charles V. Lisnahan; Oktovianus R. Nahak, T.B (JAS, 2020)
The research aim was to know the effect of l-threonine supplementation on the performance of the internal organs of broilers. This research was conducted in Kampung Bima, Kelurahan Kefa Selatan, North Central Timor Regency, and the Laboratory of the Faculty of Agriculture, University of Timor, Kefamenanu for 7 weeks, from December 2019 to January 2020. The research used 80 fourteen-day broilers. The research was designed with a Completely Randomized Design, consisting of 4 treatments and 4 replications. The dietary treatments were T0 (control feed), T1 (supplementation of 0.5% l-threonine), T2 (supplementation of 0.1% l-threonine), and T3 (supplementation of 1.5% l-threonine). The variables measured were liver weight, spleen, pancreas, gizzard, small intestinal weight, and intestinal length. Data obtained was analyzed by analysis of variance and Duncan’s test. The results showed that the levels of l-threonine significantly affected to gizzard weight, small intestinal weight, and intestinal lenght (P<0.05). It was concluded that supplementation with 1.0% l-threonine improved the digestive organ performance of broilers.